Developing instructional props to reinvent the area of parallelogram and triangle in online learning - Ketut Sarjana; Ni Made Intan Kertiyani; Laila Hayati; Baidowi Baidowi (Universitas Islam Negeri (UIN) Mataram, 2023)
[English]: For elementary school students who are still in the stage of concrete thinking, the concept of area in geometry is an abstract idea. In order to bridge the gap between concrete thinking and abstract thinking, teaching aids such as props are necessary. However, props are mostly used in face-to-face lessons, while the pandemic has forced learning to be conducted online. Employing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), this study developed a prop and instructions for using it to help students understand the area of parallelograms and triangles for online learning. Data for this study were collected through observation, interviews, validation sheets, and tests. The tryout of the props involved 281 elementary school students. The result of the study shows that the developed teaching prop provides consistent results in different classes. In addition, this prop and its manual are also effective for online learning, so teachers can use them as alternatives to assist students in reinventing the formula of the area of parallelograms and triangles. [Bahasa]: Konsep luas pada materi geometri matematika di sekolah dasar merupakan hal yang abstrak untuk peserta didik yang masih dalam tahap berpikir konkrit. Untuk menjembatani perbedaan tahap berpikir diperlukan alat bantu belajar seperti alat peraga dalam pembelajaran. Namun, alat peraga kebanyakan digunakan pada pembelajaran tatap muka, sementara pandemi menyebabkan pembelajaran harus dilakukan secara daring dari rumah. Penelitian ini mengembangkan alat peraga dan petunjuk penggunaannya untuk membantu peserta didik menentukan luas jajar genjang dan segitiga dalam pembelajaran daring. Penelitian ini menggunakan model ADDIE (Analysis, Design, Development, Implementation, Evaluation). Instrumen pengumpulan data terdiri dari lembar observasi, pedoman wawancara, lembar validasi dan tes pemahaman luas jajar genjang dan segitiga. Uji coba alat peraga melibatkan 281 siswa sekolah dasar. Hasil penelitian menunjukan bahwa alat peraga yang dikembangkan memberikan hasil yang konsisten di berbagai level kelas. Selain itu, alat peraga dan petunjuk penggunaannya juga efektif digunakan dalam pembelajaran daring sehingga dapat dijadikan referensi untuk membantu peserta didik dalam menemukan kembali rumus luas jajar genjang dan segitiga.